2008
DOI: 10.1519/jsc.0b013e318181a450
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Static Stretching on Phases of Sprint Performance in Elite Soccer Players

Abstract: The purpose of this study was to determine which phase of a 30-m sprint (acceleration and/or maximal velocity) was affected by preperformance static stretching. Data were collected from 20 elite female soccer players. On two nonconsecutive days, participants were randomly assigned to either the stretch or no-stretch condition. On the first day, the athletes in the no-stretch condition completed a standard warm-up protocol and then performed three 30-m sprints, with a 2-minute rest between each sprint. The athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 10 publications
2
24
0
9
Order By: Relevance
“…This finding supports the study of (Sayers et al, 2008) who have found that jog 800 m, forward skips 4 × 30 m, side shuffles 4 × 30 m, and backward skips 4 × 30 m wish can be considered like dynamic warm-up with excitation exercise improve acceleration phase. In the same context, Little & Williams (2006) used 3 warm-ups protocols ending with ~4 minutes of incremental intermittent sprint and agility runs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding supports the study of (Sayers et al, 2008) who have found that jog 800 m, forward skips 4 × 30 m, side shuffles 4 × 30 m, and backward skips 4 × 30 m wish can be considered like dynamic warm-up with excitation exercise improve acceleration phase. In the same context, Little & Williams (2006) used 3 warm-ups protocols ending with ~4 minutes of incremental intermittent sprint and agility runs.…”
Section: Discussionsupporting
confidence: 91%
“…In the first 20-m high speed the WU-2 protocol produced significantly faster (p < 0.05) runs than did the WU-1 protocol, no significant result was found in the other six 20-m of the successive RSA-test sprints, this may by explained with the fact that, maximum stride length only occurs when the runner has reached peak speed that is, during the maximal-speed phase, additionally during it both stride length and the stretch shortening cycle duration are at their respective greatest, in the present study the emplacement of excitation sequence at the end (WU-2) may increase this effect which observed only in the beginning in the study of (Sayers et al, 2008).…”
Section: Discussionmentioning
confidence: 50%
“…www.efsupit.ro 220 and sprint (Alikhajeh et al 2012, Chaouachi et al 2008, Fletcher & Jones 2004, Fletcher & Monte-Colombo 2010, Gelen 2010, Needman et al 2009, Sayers et al 2008, Winchester et al 2008. Papadopoulos et al 2015 have been previously reported as a result of static stretching.…”
Section: Introductionmentioning
confidence: 97%
“…Although basketball coaches follow the aforementioned warm-up type, recent studies have examined the effect of static stretching during warm-up and found detrimental impact on performance (Faigenbaum et al 2006, Fletcher & Monte-Colombo 2010, Pearce et al 2009, Fowles et al 2000, Power et al 2004, Alikhajeh et al 2012, Little & Williams 2006, Chaouachi et al 2008, ο Nelson et al 2005, Sayers et al 2008, Fletcher & Jones 2004, Gelen 2010, Needman et al 2009, Winchester et al 2008Famisis 2015, Papadopoulos et al 2015. Reductions on vertical jump performance, lower limbs' power (Faigenbaum et al 2006, Fletcher & MonteColombo 2010, Pearce et al 2009), muscle strength (Fowles et al 2000;Power et al, 2004), power (Alikhajeh et al 2012, Little & Williams, 2006, acceleration (Chaouachi et al 2008, Nelson et al 2005, Sayers et al 2008)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation